Digital Tools in ESP Learning: Culturally and Linguistically Diverse Students' Practices and Challenges - Gumartifa, Asti; Syahri, Indawan; Alfaresi, Bengawan (VELES Voices of English Language Education Society, 2025)
Integrating digital technology in English for Specific Purposes (ESP) instruction has expanded opportunities for language learning, particularly for culturally and linguistically diverse (CALD) students in non-English major programs. However, limited research has explored how these learners use internet-based tools in localised university contexts. This study investigates the use of digital technology in ESP learning among CALD students at Universitas Muhammadiyah Palembang. Employing a descriptive mixed-methods design, data were gathered through questionnaires (n=505) and focus group discussions with ESP lecturers. Findings reveal that smartphones (53%) and laptops (28%) are the most commonly used devices, with tools such as Google Translate, Chatgpt, Zoom, and Grammarly supporting English learning inside and outside the classroom. Over 63% of students rated internet tools as “very useful” for accessing field-specific materials, and 44.65% identified technology as a primary companion to classroom instruction. Students also reported gains in language proficiency, self-regulated learning, and intercultural communication. Despite these benefits, students face persistent barriers, including limited digital skills (80.6%), insufficient device access (76.8%), slow internet (66.7%), and lack of technical support (63%). Nonetheless, 68.87% of students viewed technology as helpful for future learning, and half strongly believed it promotes learning flexibility. Students also called for improved digital training (44.65%) and infrastructure (33.02%). The findings highlight the need for targeted digital support and culturally responsive content to ensure inclusive and effective ESP instruction.